Geothermal Energy in Iceland - Ragnarsson, Arni (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1996)
The annual primary energy supply in Iceland, which has a population of 268,000, is 98,000 TJ (T = 10^12) or 366 GJ per capita, which is among the highest in the world. Geothermal energy provides about 48.8% of the total, hydropower 17.2%, oil 31.5% and coal 2.5%. The main use of geothermal energy is for space heating. About 85% of all houses are heated with geothermal energy; the rest are heated mainly by electricity. So far, geothermal resources have only, to a limited extent, been used for electric power generation, because of the availability of relatively cheap hydropower resources. Of the total electricity production of 5,000 GWh in 1995, only 288 GWh or 5.8% came from geothermal energy, 94% from hydro and 0.2% from fuels